Potential Implementation of Lightweight Steel Panel System in Affordable Housing Project: Developers Perspective - Saikah, Misriyanti; Kasim, Narimah Binti; Kasim, Rozilah (International Journal of Sustainable Construction Engineering and Technology, 2020)
Utilization of Industrialized Building System (IBS) becomes increasingly dominant in the construction of affordable housing in Malaysia. Theoretically, utilization of IBS system can benefit to reduce the affordable housing price due to the less labor involvement and short constructions time. However, current IBS usage in housing construction still cannot fulfill the affordable housing demand especially in term of price and housing quality. Recent study reveals the lack adoption of IBS component in construction industry mainly caused by poor perception among stakeholder toward the system. Hence, some alterations in the supply of the IBS component essential to being prepared in order to reach the price target to permit all middle-income groups to own the quality house. Construction industry also can explore the other types of IBS system focusing on lightweight types such as wood or steel system which clearly could give benefit to the housing industry on faster works and high housing quality. Due to strong and durable characteristic of lightweight steel panel, it can be seen as an alternative component to be explored to enhance construction practices of affordable housing project. Therefore, the main purpose of this study is to identify the potential of lightweight steel panel system to be implemented for affordable housing project. Accordingly, for the highlight in reducing affordable housing price integrate with provision of good quality housing this research focus on feedback from developer about the proposed lightweight steel panel system. This research conducted an interview with six project managers with more than three years working experience in housing construction project at South of Peninsular Malaysia. Developer’s experience in affordable housing project mainly for landed house is coinciding because of lightweight steel panel system suitability for not more than two stories house. The result reveals that, respondent prefer to the advantages of lightweight steel panel system in term of faster installation works, low maintenance work, flexibility and smart construction. In conclusion, the ability of the system to decrease housing price at the same time sustain the desired quality of housing will increase ability and satisfaction for middle-income earner to own the house.